Pelatihan Inovasi Buah Naga Dan Kewirausahaan Pada Ibu-Ibu Oikumene Di Arso VII - Andarias Kuddy; Westim Ratang (UNIVERSITAS CENDERAWASIH, 2021)
Entrepreneurial success can be achieved if entrepreneurs use innovative products, processes and services as the creation of new things. So in this case, innovation is an important element to empower resources to produce something new and create value. The power of entrepreneurship as an economic driver lies in the creation of new ones to create value continuously by turning all challenges into opportunities. The objectives to be achieved from this community service activity are: to provide Oikumene mothers to have an understanding of the importance of entrepreneurship and to be able to try to process dragon fruit into dragon fruit jam and dragon fruit pudding to help their family's economy. The results show that, by following this service, it is expected that Oikumene women have an entrepreneurial spirit and dare to try to process dragon fruit into products that have added value. It is also expected that Oikumena women can support the existing family economy. It is also expected that Oikumene mothers become mothers who are formed into people who are confident, independent, creative, innovative and not easily discouraged, and able to overcome family economic problems by increasing family income.